EXAMINING THE EFFECT OF PRODUCT ASSORTMENT AND PRICE DISCOUNT TOWARD ONLINE PURCHASE DECISION OF UNIVERSITY STUDENT IN INDONESIA - Dita Amanah; Dedy Ansari Harahap (Jurnal Manajemen dan Kewirausahaan, 2018)
This study investigated the effect of product assortment and price discount on online purchase decision among university student in Indonesia. Ninety samples were employed which is students who had made an online purchase for fashion products. Purposive sampling has been applied as a sampling technique in this study. The results revealed that product assortment affected significantly to student online purchase decision. However, price discount did not affect significantly to online purchase decision. The limitation is only to test two variables of price discount and product diversity. Further studies are encouraged to consider other variables in determining online purchasing decisions such as trust, reputation, attractiveness of posting messages.